Issues of the time limit for consideration of an administrative complaint - Persheyev, Alisher; Bekturganov, Abdimanap; Tokhanova, Roza (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
Administrative relations as an area of law is an integral aspect of modern society, regulating many relationships among its constituents. Through analysis of administrative law it has been demonstrated that its regulations determine what term should be considered when considering complaints, its implementation in other spheres of law is then assessed. This article investigates issues surrounding the timeliness of administrative complaints review processes. Particular attention is given to factors that contribute to long review processes, which in turn impact administrative efficiency. Authors discuss various legal regulations, organizational features and procedural features while pinpointing key challenges they present and ways to overcome them. According to the results of legal examination, relevant concepts are evaluated; time limits for consideration of complaints, procedures and similar requirements related to other legal areas are taken into consideration, compliance with deadlines signifies the level of importance given to protecting human rights and liberties both criminally as well as administratively. Based on its findings, this paper emphasizes the significance of adhering to time limits for administrative complaints in order to maintain fairness and efficiency of administrative procedures.